Promoting electron transfer to enhance anaerobic treatment of azo dye wastewater with adding Fe(OH)3. (December 2017) - Li, Shiyang; Cao, Yi; Bi, Cancan; Zhang, Yaobin
Graphical abstract: Highlights: The Fe(OH)3 addition increased the COD removal and decoloration efficiency. Autocatalysis of azo dye via intermediates was enhanced by Fe(III)/Fe(II) cycle. Dissimilatory iron reducing bacterium enhanced the electron transfer efficiency. Abstract: In this study, Fe(OH)3 was dosed into anaerobic reactor (R1) to stimulate the electron transfer process during the decoloration treatment. As results indicated, the chemical oxygen demand (COD) removal and decoloration efficiency were increased by 61.7% and 32.0% than that of the control reactor (R2), respectively. The cyclic-voltammetric analysis of the effluent demonstrated that the cycles of Fe(III)/Fe(II) and 1-imino-2-napthoquinone/1-amino-2-napthol (oxidative/reductive state of the decoloration intermediate product) had been established in R1. The concentration of cytochrome c and the conductivity of suspended sludge in R1 were also 3.2 and 2.1 times higher than that in R2. All experiments above indicated that the electron transfer process between substrates and azo bonds was accelerated efficiently. Furthermore, the abundance of iron reducing bacteria was higher than that of R2, indicating that dissimilatory iron reduction as a reason for the Fe(III)/Fe(II) cycle played an important role in the anaerobic decoloration treatment.